2004
DOI: 10.2337/diacare.27.12.2887
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Statin Therapy Does Not Alter the Progression of Intima-Media Thickness in Patients With Type 2 Diabetes Without Manifest Cardiovascular Disease

Abstract: OBJECTIVE -Cardiovascular disease (CVD) is the most important cause of mortality in patients with type 2 diabetes. We aimed to determine the effect of statin therapy versus placebo on the progression of carotid intima-media thickness (IMT) in type 2 diabetic patients without manifest CVD. RESEARCH DESIGN AND METHODS-A randomized, placebo-controlled, doubleblind clinical trial was performed in 250 patients with type 2 diabetes. Patients were given either 0.4 mg cerivastatin or placebo daily. In August 2001, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 43 publications
3
64
1
4
Order By: Relevance
“…At the end of 2 years of follow-up, there was no difference in the progression of carotid artery IMT, although the number of cardiovascular events was significantly smaller (Pϭ0.006) in patients treated with statins. The findings by Beishuizen et al 30 were therefore consonant with those of the Heart Protection Study 31 and the Collaborative Atorvastatin Diabetes Study (CARDS), 32 in which statins significantly reduced events in diabetes. The reason there was a difference in imaging end points between the abovementioned IMT study and our CT-based study is unclear.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…At the end of 2 years of follow-up, there was no difference in the progression of carotid artery IMT, although the number of cardiovascular events was significantly smaller (Pϭ0.006) in patients treated with statins. The findings by Beishuizen et al 30 were therefore consonant with those of the Heart Protection Study 31 and the Collaborative Atorvastatin Diabetes Study (CARDS), 32 in which statins significantly reduced events in diabetes. The reason there was a difference in imaging end points between the abovementioned IMT study and our CT-based study is unclear.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, diabetes mellitus is associated not only with atherosclerotic calcification in the subintimal space, but also with calcification of the tunica media of the vessel wall, 28,29 which also poses a substantial risk of cardiovascular events in these patients. 29 Our results are partly discordant with those published by Beishuizen et al 30 These investigators used sequential carotid artery intima-media thickness (IMT) measurements to assess the effect of statin therapy compared with placebo in 250 type 2 diabetes patients. At the end of 2 years of follow-up, there was no difference in the progression of carotid artery IMT, although the number of cardiovascular events was significantly smaller (Pϭ0.006) in patients treated with statins.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Similarly, the TG levels were significantly reduced, by 11.9% in the pitavastatin group (P<0.05) and by 13.6% in the LDL-C reduction in response to each statin 23) , we estimated the carotid IMT changes with statin treatment for 3 years to be −0.026 mm in the pitavastatin group and 0.008 mm in the pravastatin group, and the standard deviation for IMT change was 0.0708 mm. According to a previous report focusing on type 2 diabetes 24) , we estimated that 54 participants in each group would be required for 0.8 power at the alpha level of 0.05 for a one-sided test. Therefore, we enrolled 60 subjects in each group.…”
Section: Statin Effects On Lipid Profilementioning
confidence: 99%
“…9 In contrast, only 4 studies failed to confirm the effect of statins (namely, cerivastatin and pravastatin) on IMT. [10][11][12][13] As an example, we mention the study by Ito et al, which showed that cerivastatin and pravastatin did not improve carotid IMT after 6 months of treatment. 10 A possible explanation for the negative results of the Mizuguchi trial could be the modest duration of follow-up, although this same duration was sufficient to demonstrate a positive effect on IMT in many statin trials.…”
Section: Letter By Ntaios Et Al Regarding Article "Impact Of Statin mentioning
confidence: 98%